Goethite Nanofibers /CNTs based Nanocomposites Synthesized by Free-Template Hydrothermal Method and their Physico-Chemical Properties for Energy Storage Application - S. Djelamda, F. Djefaflia, A. Harat, A. Nait-Merzoug, D. Momodu, M. Manyala, M. Guerioune and O. Guellati (ENP Engineering Science Journal, 2023)
In this investigation, we report the synthesis of Goethite-NFs/CNTs nanocomposites using hydrothermal method at optimized growth condition. These nanostructured products have been characterized in order to identify their physico-chemical properties by different techniques, such as: X-Ray Diffraction (XRD), Raman Spectroscopy, High Resolution Scanning Electron Microscopy (FESEM), Thermal analysis (TGA/DTA) and UV- Vis Spectroscopy. The obtained Goethite nanofibers (NFs) have shown structured triangular base nanofibers with diameter in the range [181 - 363 nm]. Using nested and twisted CNTs (MWNTs type) but fairly homogeneous in diameter around 48 nm, the formation of an assembly of two forms (MWNTs and iron oxide Nanofibers) in nanocomposite configuration confirms the significant improvement of their physico-chemical properties, like the increase in their electrical conductivity proven by their obtained gap energy Eg from 3.12 to 2.50 eV. Consequently, the reached results prove clearly that this kind of iron oxide-NFs/MWNTs based nanocomposites can be excellent candidate as electroactive nanomaterials for energy storage application.